Transcriptional repression by Drosophila and mammalian Polycomb group proteins in transfected mammalian cells. - Bunker, C A (1994)
The Polycomb group (Pc-G) genes are essential for maintaining the proper spatially restricted expression pattern of the homeotic loci during Drosophila development. The Pc-G proteins appear to function at target loci to maintain a state of transcriptional repression. The murine oncogene bmi-1 has significant homology to the Pc-G gene Posterior sex combs (Psc) and a highly related gene, Suppressor two of zeste [Su(z)2]. We show here that the proteins encoded by bmi-1 and the Pc-G genes Polycomb (Pc) and Psc as well as Su(z)2 mediate repression in mammalian cells when targeted to a promoter by LexA in a cotransfection system. These fusion proteins repress activator function by as much as 30-fold, and the effect on different activation domains is distinct for each Pc-G protein. Repression is observed when the LexA fusion proteins are bound directly adjacent to activator binding sites and also when bound 1,700 bases from the promoter. These data demonstrate that the products of the Pc-G genes can significantly repress activator function on transiently introduced DNA. We suggest that this function contributes to the stable repression of targeted loci during development.